The Importance Of Marriage The Importance Of Marriage Isbat And The Prevention Of Early Marriage In Sedau Village, Narmada West - Fahrurrozi, Muhammad; Hatimah, Husnul; Fidiawati, Fidiawati; Aulia, Nanda Rizky (State Islamic University of Mataram, 2023)
The purpose of this article is to explain the importance of marriage isbat and the prevention of child marriage in Sedau Village, Narmada District, West Lombok Regency. The method used is the method of distributing information through socialization and action by collecting data on the marriage certificate. The results of the research conducted show that there are still many people in Sedau Village who do not have a marriage book or whose marriage has not been registered with the KUA. In addition, there are still many cases of early marriage in Sedau Village, which are influenced by several factors, including low education, economic, environmental, and other factors. As a result, maximum efforts from all elements of society—both parents, the environment, religious leaders, and especially village policies—are required to overcome problems associated with early marriage.